Monitoring of Vitiligo Patches Over 6 Months to Validate Dermoscopic Findings of Lesional Stability - Chitra Kamath; Rachita Dhurat; Bhavika Shah; Richa Sharma; Priyanka Arun Kowe; Sachin Chamle (Mattioli1885, 2023)
Background: Previously laid down criteria for lesional stability of vitiligo are inconsistent. Longitudinal data on correlation between dermoscopic features of vitiligo and disease activity is limited. Objective: To sequentially determine the dermoscopic features of vitiligo and to assess their association with the dynamic nature of the vitiligo patch. Methods: Sixty patients with 200 vitiligo patches fulfilling the inclusion criteria on medical therapy were subjected to sequential clinical and dermoscopic examination for 6 months. Baseline lesional photographs, dermoscopy and tracing of the patch was made and repeated at 6 months. The follow up tracing was superimposed onto the baseline tracing. Based on the increase or decrease in size, their outcomes were grouped as responsive, progressive and quiescent. Paired analysis of dermoscopic features was done between baseline, and their follow up after 6 months. Results: Well defined border was associated with static nature of the vitiligo patch and ill-defined borders and trichrome pattern depicted its dynamic nature. Statistically significant increase in leukotrichia and satellite lesions amongst progressive patches and a decrease amongst responsive patches was observed. Pigment network changes were statistically significant for both responsive and progressive patches. Satellite lesions and micro-Koebner's phenomena was suggestive of progressive disease, while perifollicular pigmentation and perilesional hyperpigmentation was suggestive of repigmenting disease and proved to be an early marker for response to therapy. Conclusions: Repeated dermoscopic evaluation of lesions in a serial manner to assess disease activity helps understand their evolving nature and is a valuable tool in planning appropriate further treatment.